2020
DOI: 10.1016/j.jphotochem.2019.112338
|View full text |Cite
|
Sign up to set email alerts
|

Effect of linker length on the spectroscopic properties of bacteriochlorin – 1,8-naphthalimide conjugates for fluorescence-guided photodynamic therapy

Abstract: Conjugation of 4-pyrazolinyl-1,8-naphthalimide and propargyl-15 2 ,17 3 -dimethoxy-13 1 -amide of bacteriochlorin e by the oligo(ethylene glycol) linker resulted in the dual function system comprising the modalities of a photosensitizer and a fluorescence imaging agent. In comparison with the conjugate of the same structure but containing the shorter linker, the system demonstrated the higher emission intensity originating from the naphthalimide unit, which could be explained by the decrease in resonance energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…A significant drawback of all currently described photosensitizer–linker–fluorophore conjugates which limits their appliance is the process of resonance energy transfer (RET) between chromophores [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Depending on the direction of this process, it leads either to fluorescence quenching of the fluorophore (when RET occurs from fluorophore to photosensitizer) [ 5 , 6 , 7 , 8 , 9 , 10 ] or to a significant decrease in the photodynamic efficiency of the photosensitizer (RET from photosensitizer to fluorophore) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant drawback of all currently described photosensitizer–linker–fluorophore conjugates which limits their appliance is the process of resonance energy transfer (RET) between chromophores [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Depending on the direction of this process, it leads either to fluorescence quenching of the fluorophore (when RET occurs from fluorophore to photosensitizer) [ 5 , 6 , 7 , 8 , 9 , 10 ] or to a significant decrease in the photodynamic efficiency of the photosensitizer (RET from photosensitizer to fluorophore) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A significant drawback of all currently described photosensitizer–linker–fluorophore conjugates which limits their appliance is the process of resonance energy transfer (RET) between chromophores [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Depending on the direction of this process, it leads either to fluorescence quenching of the fluorophore (when RET occurs from fluorophore to photosensitizer) [ 5 , 6 , 7 , 8 , 9 , 10 ] or to a significant decrease in the photodynamic efficiency of the photosensitizer (RET from photosensitizer to fluorophore) [ 11 ]. In the publications [ 9 , 10 , 11 ], the influence of the spacer fragment length on the energy transfer efficiency in conjugates was considered and it was shown that an increase in the number of methylene or ethylene glycol units in the spacer composition leads to a slight decrease in the energy transfer efficiency, and the resulting conjugates do not allow imaging and phototherapy modes to be performed independently.…”
Section: Introductionmentioning
confidence: 99%
“…Primarily PDT is universally utilized in oncology for identification and visualization of tumor cells at the cellular and molecular levels. PDT encompasses the physics of dosimetry, the chemistry of synthesizing photosensitizer drugs with strong absorption of light in the region of the therapeutic window, and the biological pathway of inhibition/reduction of tumor growth. Thus, an interplay of sciences contributes toward tumor-targeting, imaging, and therapy.…”
Section: Optical Principle Of Photodynamic Therapymentioning
confidence: 99%
“…43 There are a few examples of bichromophoric pyrazolines. [44][45][46][47][48][49][50][51][52][53][54] Ji studied examples with carbazole, 44 triphenylamine 45 and aromatic substituents at the 5-position. 46 These studies also demonstrated the tuning of blue emitting 1,3,5-triphenyl-D 2 -pyrazolines 47,48 into green emitting molecules by extension of the p-conjugation at the 1-phenyl position.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37] Lu reported naphthalimide-pyrazoline polymers based on ICT and aggregation-induced emission. 55- 57 Rurack 51 and Fedorova 52,53 presented near infra-red (NIR) ionophores and research by Xie described pyrazoline-BODIPY nanoparticles. 54 In none of these studies, however, were the molecules or materials examined in the context of molecular logic-based computation.…”
Section: Introductionmentioning
confidence: 99%